Analgesic tolerance to morphine is regulated by PPARγ. (December 2014) - de Guglielmo, Giordano; Kallupi, Marsida; Scuppa, Giulia; Stopponi, Serena; Demopulos, Gregory; Gaitanaris, George; Ciccocioppo, Roberto
<x xml:space="preserve">Abstract</x> Background and Purpose Opioid drugs are potent analgesics. However, their chronic use leads to the rapid development of tolerance to their analgesic effects and subsequent increase of significant side effects, including drug dependence and addiction. Here, we investigated the role of PPARγ in the development of analgesic tolerance to morphine in mice. Experimental Approach We monitored analgesia on alternate days using the tail immersion test. Key Results Daily administration of morphine (30 mg·kg−1, bid) resulted in the rapid development of tolerance to thermal analgesia. Co‐administration of pioglitazone (10 and 30 mg·kg−1, bid) significantly attenuated the development and expression of tolerance. However, pretreatment with GW‐9662 (5 mg·kg−1, bid), a selective PPARγ antagonist, completely abolished this effect. Injection of GW‐9662 and a lower dose of morphine (15 mg·kg−1, bid) accelerated the development of tolerance to its antinociceptive effect. Subsequently, we found that conditional neuronal PPARγ knockout (KO) mice develop a more rapid and pronounced tolerance to morphine antinociception compared with wild‐type (WT) controls. Moreover, in PPARγ KO mice, pioglitazone was no longer able to prevent the development of morphine tolerance. Conclusions and Implications Overall, our results demonstrate that PPARγ plays a tonic role in the modulation of morphine tolerance, and its pharmacological activation may help to reduce its development. These findings provide new information about the role of neuronal PPARγ and suggest that combining PPARγ agonists with opioid analgesics may reduce the development of tolerance and possibly attenuate the potential for opioid abuse.